Information management as a field of scientific and practical activity - Sayyora Abdulkhakovna Zakirova; Kamol Khadjayev (Research Parks Publishing LLC, 2021)
The sphere of information management is a set of all decisions necessary for management at all stages of an enterprise's life cycle, including all actions and operations associated with information in all its forms and states, and with the enterprise as a whole. At the same time, the tasks of determining the value and efficiency of using not only the information itself (data and knowledge) should be solved, so that each manager receives only relevant information, but also other resources of the enterprise, in one way or another, coming into contact with information: technological, personnel, financial, etc., is taught as an innovative specialty. This article examines information management as a field of scientific and practical activity.